Improved aerodynamic design of small wind turbine blades - عيسى, أويس; رامي جورج,; بدر الدين عابدين , (Latakia University Journal -Engineering Sciences Series, 2024)
The research aims to improve the aerodynamic design small Horizontal-Axis-Wind-Turbine blades to work at low wind speeds and at low flow of Reynolds number through testing the improvement method based on the use of two different airfoils along the length of the blade with the aim of increasing the capacity coefficient where the final shape of the improved blade is made of the two airfoils SD7062 and NACA23012. In this research, we followed an analytical methodology based on modeling and simulation whereby an algorithm depends on the blade's element momentum theory BEMT was formed to extract the ideal aerodynamic parameters of the blades due to the design conditions. At the beginning, two blades of each profile were designed separately based on the BEMT algorithm, and their performance was analyzed within the range of an assumed wind speed (7-4) V=m/s and the range of tip velocity ratio λ=[1-10], after that the two airfoils modified blade was designed and its performance was and its performance was analyzed at the same previous circumstance. We performed an aerodynamic simulation of the enhanced two_ profiles blade in the ANSYS program using the CFD methodology depending on the possibility coefficient, the turbulence model (Shear Stress Transport) k-ω sst was selected. The simulation results in MATLAB, ANSYS and QBLADE program showed that the capacity coefficient of the improved two airfoils blade was 0.42 at a wind speed of 7m/s and a tip speed ratio of λ = 7, while it was 0.38 for the turbine with the NACA23012 airfoil, and 0.35 for the turbine with the SD7062 airfoil, hence, the results of the modeling and simulation in the three programs were matched.